Identifying the consequences of corona pandemic in children and adolescent female athletes based on the lived experience of parents and girls athletes - Zare abandansari, Mohammad; Mohamzadeh, Mehrdad; Rezapour, Fatemeh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The corona pandemic disrupts many of a person’s daily sports activities; and had devastating effects on athletes, especially female and child athletes. Identifying the negative consequences of this problem and providing practical solutions using the lived experiences of people related to the subject of the present study was. Methods: This is a qualitative, applied research and was conducted using the phenomenological approach in the Colaizzi method in 2021. The statistical population includes people related to the subject; Parents (sports coaches and faculty members) and female athletes were children and adolescents who were directly related to the research topic. Purposeful sampling method and as long as it was possible to extract completely non-repetitive concepts from the interviews; 18 interviews were conducted in a semi-structured environment in the natural environment in Mazandaran province. Results: By analyzing research information; the negative consequences of corona on female athletes 61 basic concepts and 4 sub-themes; it has psychological, social and communication effects, physical, leisure and recreational. Conclusion: Considering the negative consequences of the research, it is necessary to deal with it such as; Establishing a deeper emotional relationship between parents and female athletes, creating a calm and non-violent environment at home, increasing social support by adults, continuous assessment of the mental and physical condition of female athletes, creating a happy atmosphere at home, parents paying attention to bedtime Athlete girls, pay attention to changes in individual behaviors, strengthen communication skills, parental supervision over the use of social networks by female athletes, and play mental and motor games at home to deal with the negative consequences of coronation on female athletes.